Analisis Aspek-Aspek Yang Mempengaruhi Harga Diri Peserta Didik - Winoto Winoto; Andi Riswandi Buana Putra (Suluh: Jurnal Bimbingan dan Konseling, 2018)
The objectives in this study are: analysing the aspects that affect the self-esteem of students in Marikit Middle School 1. The population in this study amounted to 254 students. The total sample consisted of 63 students. Sampling is determined by random sampling technique. Data collection techniques use observation, and scale aspects that affect self-esteem, data analysis techniques using the percentage formula. The results of the study show that the self-esteem of students in Marikit Middle School tends to be low. The aspects that affect students' self-esteem are weak, namely: 1) Feelings of quality aspects, (the small category that is 51%); 2) Aspects of feeling capable (medium category, ie 57%); and 3) Feelings accepted (a low grade that is 39%). Based on the results of the analysis of aspects of self-esteem possessed by students in 1 Marikit Middle School tend to be low influenced by elements of feelings of worth and characters of feeling accepted.